Control-synthesized ultrafine Au nanoparticles by Aspergillus niger extracellular metabolites from SIM cards as high-effective 4-nitrophenol degradation catalyst. Issue 6 (December 2022) - Liu, Chang; Li, Guang; Ma, Enyang; Zeng, Feng; Wu, Tao; Chen, Kexin; Fan, Puyang; Wen, Xinwei; Li, Lei; Qu, Qing
Abstract: Biosynthesized Au nanoparticles are hopeful to solve the problem of 4-nitrophenol (4-NP) pollution. However, inconvenient post treatments and difficult shape control of microbial synthesized Au nanoparticles limit their practical use. Therefore in this work, ultrafine Au nanoparticles (bio-AuNPs, ∼1.6 nm) are facilely and controllably prepared by Aspergillus niger extracellular metabolites from Au(III) solution of subscriber identity module (SIM) cards. Shape control of ultrafine morphology realized by preventing the growth after nucleation is helpful to maximize the utilization of Au. Removal and recovery rates of the reaction reach 81.72% and 72.45% respectively. Without shape-controlling, complex morphologies (complex-bio-AuNPs) will be obtained. Exploration of the mechanism further proves that tryptophan residues of fungal metabolites serve as the reducing species. In 4-NP degradation catalysis, bio-AuNPs exhibit excellent reusability and much higher intrinsic activity (1.667 × 10 6 s −1 ·mol −1 ) than commercial Pd/C, complex-bio-AuNPs and reported Au materials due to the size effect. This work provides a sustainable way to recover and reuse metal resources simultaneously, and is helpful to enlighten more studies on rational design of nanoparticles in biosynthesis. Graphical Abstract: ga1 Highlights: Ultrafine bio-AuNPs was facilely control-synthesized by fungal metabolites. Shape control was realized by hindering the growth of Au nucleus. Tryptophan residues were proven to be the reducing species. Bio-AuNPs exhibited excellent intrinsic catalytic activity due to size effect.